Smart Pathfinder for Helping Blind People - Abu-arish, Israa; Baradiyyah, Alaa; ' Aburayyan, Taima (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2021)
One of the main problems that blind people face is getting around in and out of their homes. Therefore, we will develop the blind stick to act as a pathfinder that helps the blind in their lives as much as possible by taking a picture of the place where they are by using the pi camera, then by using image processing technology the objects will be detected on that image. At the same time, the system will search for the characters on the street label with the street name. Next, the blind receives movement and warning instructions. Therefore, according to the instructions reached to the blind man, he will move. The distance sensors will detect if there are closely surrounding objects to alert and warn the blind about them. Thus, this system will provide the blind with a safer environment and will give them a sense of independence which will help them lead a normal life.
no of pages 55, هندسة حاسوب13/2021
Keywords: Blind People; Smart Pathfinder